Hubungan Dukungan Keluarga Dengan Perilaku Distres Pada Pasien Diabetes Di Rumah Sakit Moewardi - Wardani, Dewi Kusuma; , Arum Pratiwi, S.Kp., M.Kes (2017)
Diabetes mellitus (DM) is a chronic disease that will be sustained over a lifetime, making the diabetic patients suffering from depression. Depression in patients with diabetes mellitus will result in poor blood sugar control, the lack of support from family, as well as the worry of complications of diabetes People with diabetes who are depressed will bring up some of the responses, one of which is a behavioral response. So, we need the support of the family to prevent the onset of prolonged stress. This study aims to determine the relationship between family support with behavioral distress in diabetic patients at Hospital Dr. Moewardi. The design of this study design deskriptive corelative. The study population was patients with diabetes who undergo outpatient Internal Medicine Polyclinic Hospital Dr. Moewardi. Sampling using purposive sampling with a sample of 41 patients. Collecting data using questionnaires Hensarling Diabetes Family Support Scale (HDFSS) and the Diabetes Distress Scale (DDS). Data were analyzed using Pearson product moment correlation test, with a correlation coefficient (r) of -0.776 with a significance level(p-value= 0.002). The study concluded that there is a relationship between family support with behavioral distress in diabetic patients at Hospital Dr. Moewardi. The correlation coefficient is negative which indicates that the support of family and behavioral distress in the opposite direction, so that a high family support resulted in poor behavior of distress. Conversely, low family support resulted in higher behavioral distress. Keywords: distress behavior, family support, diabetes mellitus type 2